Three new species of the seasonal killifish genus Simpsonichthys, subgenus Hypsolebias (Teleostei: Cyprinodontiformes: Rivulidae) from the rio Paracatu drainage, rio São Francisco basin, Brazil - Costa, Wilson J.e.m.; Brasil, Gilberto C. (Zootaxa, 2006)
Three new species of the neotropical seasonal killifish genus Simpsonichthys are described from the middle rio Paracatu drainage of the middle rio São Francisco basin, Brazil. Simpsonichthys virgulatus is a typical member of the S. notatus species group, diagnosed by the derived A-pattern frontal squamation and presence of blue spots on distal margin of the dorsal fin in males. It is similar to S. trilineatus and S. auratus in having the anterior portion of the flanks golden, with dark brown to black blotches in males, and differs from those species by having more blotches on the flank, bars present on the caudal peduncle, and hyaline pectoral fins in males. Simpsonichthys fasciatus is similar to S. alternatus and S. delucai in having the combination of anal fin rounded in males and anal fin spatula-shaped in females, but differs in having the dorsal-fin origin anteriorly positioned and a dark gray to black stripe on the distal margin of dorsal fin in males. Simpsonichthys gibberatus differs from all other congeners by the pronounced and convex profile of the anterodorsal portion of the body in females.